RISK ASSESSMENT OF OPEN PIT SLOPE DESIGN AT PT ADARO INDONESIA - M. A. Azizi; S. Kramadibrata; R. K. Wattimena; I. D. Sidi (Puslitbang tekMIRA, 2014)
Risk assessment of open pit slope stability is an important aspect to be considered in a decision making of slope design. The risk of slope failure that occurred on the slopes of the mine affect two factors namely the failure probability (FP), and consequences (C) of slope failure. FP is obtained from the collection of the value of Safety Factor (SF) < 1 compared to the total value of SF, while the consequences is estimated from the sectional area multiplied by the width of slope failure. Physical and mechanical properties of sandstone was collected from PT Adaro Indonesia, and tested by “Kolmogorov-Smirnov (K-S)” fitting method to obtain an assumed theoretical distribution that be sued with the character of the original distribution data. “Monte Carlo (MC)” and “Latin Hy- percube (LH)” sampling method is used as a tool to generate sample data, and both methods were compared. Finally Validation is conducted in order to propose an acceptable criteria of FP for single slope of sandstone.